2013
DOI: 10.1155/2013/869398
|View full text |Cite
|
Sign up to set email alerts
|

The Time Course Effects of Electroacupuncture on Promoting Skeletal Muscle Regeneration and Inhibiting Excessive Fibrosis after Contusion in Rabbits

Abstract: The aim of this study was to investigate the longitudinal effects of electroacupuncture (EA) on Zusanli (ST36) and Ashi acupoints in promoting skeletal muscle regeneration and inhibiting excessive fibrosis after contusion in rabbits. Sixty rabbits were randomly divided into four groups: normal, contusion, EA, and recombinant human insulin-like growth factor-I (rhIGF-I). An acute skeletal muscle contusion was produced on the right gastrocnemius (GM) by an instrument-based drop-mass technique. EA was performed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
0
10
1
Order By: Relevance
“…In aged muscles the disturbance in redox status and expression of antioxidant enzymes was also reported (Fulle et al 2004 ). Apart from that, the reverse correlation between total SOD activity and progression of fibrosis in skeletal muscle was also shown (Wang et al 2013 ). Although HO-1 reduces expression of TGF-β (Stachurska et al 2013 ), and lack of Nrf2 causes extensive muscular fibrosis after myotrauma (Al-Sawaf et al 2014 ), the potential antifibrotic effect of HO-1 in skeletal muscle regeneration was not so far examined.…”
Section: The Complex Role Of Oxidative Stress and Antioxidant Enzymesmentioning
confidence: 94%
“…In aged muscles the disturbance in redox status and expression of antioxidant enzymes was also reported (Fulle et al 2004 ). Apart from that, the reverse correlation between total SOD activity and progression of fibrosis in skeletal muscle was also shown (Wang et al 2013 ). Although HO-1 reduces expression of TGF-β (Stachurska et al 2013 ), and lack of Nrf2 causes extensive muscular fibrosis after myotrauma (Al-Sawaf et al 2014 ), the potential antifibrotic effect of HO-1 in skeletal muscle regeneration was not so far examined.…”
Section: The Complex Role Of Oxidative Stress and Antioxidant Enzymesmentioning
confidence: 94%
“…However, DN mediated mechanotransduction of fibroblasts may be able to help remodel painful tissue by dampening tissue tension via actin polymerization [110]. A number of studies have demonstrated the use of DN to reduce pain associated with scar [58,113] and fibrotic tissue [114] further supporting this possibility.…”
Section: Dry Needling Mechanotransduction and Tissue Restructuringmentioning
confidence: 99%
“…Researchers have shown that EA can significantly promote tissue repair in such contexts as myocardial infarction, nerve regeneration, and wound healing [ 12 - 15 ]. Moreover, EA can also accelerate muscle regeneration and improve the quality of repair after skeletal muscle injury [ 6 ]. Our previous studies showed that EA treatment reduces the expression of both GDF-8 and p-Smad2/3, decreases the formation of fibrotic tissue in injured muscle, increases the expression of myosin heavy chain (MHC), and enhances the capillary density at injured sites, thereby improving muscle fiber regeneration [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EA can also accelerate muscle regeneration and improve the quality of repair after skeletal muscle injury [ 6 ]. Our previous studies showed that EA treatment reduces the expression of both GDF-8 and p-Smad2/3, decreases the formation of fibrotic tissue in injured muscle, increases the expression of myosin heavy chain (MHC), and enhances the capillary density at injured sites, thereby improving muscle fiber regeneration [ 6 ]. However, whether EA can promote the functional recovery of skeletal muscle is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation